Microeconomic mechanisms behind export spillovers from FDI: Evidence from Bulgaria - Andrea Ciani; Michele Imbruno (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
This paper studies how the presence of multinational enterprises affects the export performance of Bulgarian manufacturing firms - Export spillovers from FDI. Using export data at the firm/product/destination level for the period 2004-2006, we find positive forward spillover on export value and quantity, related to quality upgrading. Conversely, we find negative (or insignificant) backward and horizontal spillover on export flows, related to quality downgrading. When aggregating data at the firm level and considering that a firm can operate in several sectors, we show that the presence of foreign input suppliers allows domestic firms to export additional varieties of lower quality and upgrade the average quality of existing varieties, whereas the presence of foreign customers generates the opposite effect.
Keywords: F14; F23; F61; 330; Export spillover; FDI; Multi-product firms; Unit value; Quality